Jamming-resilient control and communication framework for cyber physical systems - Tomic,I; Breza,M; McCann,J (IET, 2020)
The control and monitoring of large infrastructure installations is becoming smarter, cheaper to run and easier to managethrough the use of wireless sensor and actuator networks (WSANs). Cyber Physical Systems (CPSs)are the combination of cyber sensing via WSANs and physical control. The problem withthe use of WSANs in CPSs is that they make the whole system being controlled exposed to the world andvulnerable to theft or cyber-attacks.In this article we examine the failure of CPS infrastructure due to intelligent radio jamming.The intelligent jammer employs a protocol-aware jamming strategy to learn the transmission period of a sensor device.It then broadcasts noise to disrupt the wireless communication and destabilise the CPS.Wepresent a CPS control and communication approachto counter thethreat of intelligentradio jamming. The approach exploitsthe properties of the event-based controlstrategy combined with a reservation-based communication protocolthat employs obfuscation. We usea physical model of a water distribution networkto demonstrate that the approachis resilient to an intelligent jamming attack, it is able to continue normaloperationof the systemand maintain the desired level of performance while achieving low overheads.